Identification of RNA silencing suppressor encoded by citrus chlorotic dwarf-associated virus - Ye, Xiao; Ding, Dongdong; Chen, Yuan; Liu, Chuang; Li, Zhongan; Lou, Binghai; Zhou, Yan (Frontiers in Microbiology, 2024)
Introduction: Citrus chlorotic dwarf-associated virus (CCDaV) is an economically important citrus virus associated with leaf curling, deformation, and chlorosis in China. Plants have evolved RNA silencing to defend against viral infections; however, the mechanism by which CCDaV suppresses RNA silencing in citrus is unknown.Methods: All six proteins encoded by CCDaV were ectopically expressed in Nicotiana benthamiana 16c using the pCHF3 vector to identify RNA-silencing suppressor activities.Results: V2 protein encoded by CCDaV suppressed local RNA silencing and systemic RNA silencing triggered by GFP RNA, but did not impede short-distance movement of the RNA silencing signal in N. benthamiana 16c. GFP fluorescence observations showed that the ability of V2 to suppress RNA silencing was weaker than tomato bushy stunt virus P19. Deletion analysis showed that the putative nuclear localization signal (NLS, 25-54 aa) was involved in RNA silencing suppression activity of V2. Furthermore, V2 can not block dsRNA-triggered RNA silencing. The subcellular localisation assay suggested that V2 was localized to both, nucleus and cell membrane of N. benthamiana.Overall, the results of this study demonstrate that CCDaV-V2 acts as an activity of silencing suppressor. This is the first reported RNA-silencing suppressor encoded by Citlodavirus and will be valuable in revealing the molecular mechanism of CCDaV infection.